Stress Drop Analysis on Banda Sea - Yuliatmoko, R. S.; Kurniawan, T.; Kambali, R. A. P. (Jurnal Pendidikan Fisika Indonesia, 2020)
Stress drop is a fundamental parameter of earthquake source that describes stress before and after an earthquake. The purpose of this study was to determine the tectonic characteristics of the Banda sea region. The research method used is a mathematical analysis and Nelder Mead Simplex nonlinear inversion methods. The results show that the Banda Sea is the area with complex tectonic conditions and large earthquake impacts. The Banda sea earthquake generated a stress drop of between 2 MPa -10 MPa from small to medium, it can be concluded that the rocks in the Banda Sea are relatively harder because the Banda Sea has a complex and varied oceanographic profile. The Banda Sea contains many continental fragments and has very deep ocean basins in the North Banda and Weber Deep, as well as plate rollbacks that form geometry in the shape of a spoon. The strength of rocks in the Banda Sea is also strengthened by the results of gravitational anomalies, there are significant differences in the gravity anomalies around the Banda ocean which indicate high density. This information is very important to know the amount of pressure released shortly after the earthquake which has a very large impact as a disaster mitigation measure.Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â